Measuring the oscillator strength of intercombination lines of helium-like V ions in a laser-produced-plasma - Pérez-Callejo,G; Jarrott,LC; Liedahl,DA; Schneider,MB; Wark,JS; Rose,SJ (Journal of Quantitative Spectroscopy and Radiative Transfer, 2020)
We present results of measurements of the oscillator strength of intercombination lines of He-like Vanadium ions in high energy density (HED) laser-produced-plasmas and compare them with the simulations from commonly used codes and data from the NIST database. Whilst not yet sufficiently accurate to constrain different trusted atomic-physics models for the particular system studied, our results are in agreement with the available data within experimental error bars, yet differ from cruder approximations of the oscillator strength used in certain atomic-kinetics packages, suggesting that this general method could be further extended to be used as a measurement of the oscillator strength of additional atomic transitions under the extreme conditions that are achieved in HED experiments.